Disease History and Delayed Diagnosis of Dengue Infection as Risk Factors for Dengue Shock Syndrome in Wangaya Hospital Denpasar - I Made Suganda Yatra; I Wayan Gede Artawan Eka Putra; Gede Ngurah Indraguna Pinatih (Universitas Udayana, 2015)
Background and purpose: Dengue Haemorrhagic Fever (DHF) is a serious public health concern in Bali Province, especially in Denpasar wherein the incidence rate amounted to 217.7 per 100,000 in 2014. This figure is much higher than national incidence of 51 per 100,000. Dengue Shock Syndrome (DSS) frequently occur alongside high mortality. This research aims to identify risk factors of DSS among DHF patients hospitalized in Wangaya Hospital Denpasar. Methods: A case-control study was conducted. Cases (47) were DSS patients and controls (94) were dengue patients hospitalized in Wangaya Hospital in 2013- 2014. Data were collected from medical records on as age, gender, duration of fever, dengue history, haematocrit, platelets, class of care and health insurance. Results: Risk factors that independently associated with DSS were history of previous dengue infection with adjusted OR=11.6 (95%CI=1.83-73.96), duration of fever before admission ≥4 days with adjusted OR=5.5 (95%CI: 2.03-14.96), haematocrit ≥42% with adjusted OR=2.8 (95%CI: 1.02-7.68), platelets <50,000/mm3 with adjusted OR=5.2 (95%CI: 1.88-14.36), and third class ward with adjusted OR=2.9 (95%CI: 1.01-8.29). Conclusion: History of previous dengue infection and delay in recognizing the symptoms of dengue fever increased risk of DSS. In addition, patients who hospitalized in the third class ward had higher risk of DSS.